KEWENANGAN BADAN PENGAWAS OBAT DAN MAKANAN TERHADAP PERDA PROVINSI BALI NO 5 TAHUN 2012 TENTANG PENGENDALIAN PEREDARAN MINUMAN BERALKOHOL - I Putu Mahentoro (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
ABSTRACTThe research was conducted based on the same authority which is ownedby the two institutions, namely Food and Drug Administration of the Republic ofIndonesia and Bali Provicial Government in monitoring and controlling ofalcoholic beverages in Bali.The results of this study demonstrate the Food and Drug Administrationand the Provincial Government of Bali have the same authority to supervise andcontrol alcoholic beverages in Bali. Bali Local Government Regulation Number 5of 2012 on the Circulation of Alcoholic Beverage Control only requires each hasa label on alcoholic beverages issued by the Government of Bali has to bedistributed to the public, while the authority of the Food and Drug Administrationis regulated in the Regulation of Minister of Health of the Republic of IndonesiaNumber 382/MENKES/PER/VI/1989 on Registration of Food that requires allfood produced both by local producers and imported foods are required to beregistered to the Ministry of Health through the Food and Drug Administration.In the Regulation Number 5 Year 2012 did not include the authority of theFood and Drug Administration (the Empty Norms) so that the Food and DrugAdministration can not perform optimally the law enforcement againstmanufacturers, distributors and sellers of alcoholic beverages in violation. Tocope with the condition it should be a amendment in the Bali ProvincialRegulation Number 5 of 2012 by stating firmly and clearly the authority of theFood and Drug Administration related to the registration of food, which requiresthat for all foods and beverages that will be distributed to the public must beregistered to the Ministry of Health through the Food and Drug Administration.